Maritime Cargo Operations - Olsen, Alexander Arnfinn (Routledge, 2023)
Maritime Cargo Operations introduces the core concepts of cargo work for marine engineering students and cadets. It provides enough detail to provide a sound basis for a future career, and is built around the essential principles of the maritime profession. Each subject area begins with a learning outcome and ends with self-test questions. It also offers a general overview for deck officers.